Effect of simultaneous intake of rare sugars allitol and D-allulose on intra-abdominal fat accumulation in rats - Matsuo, Tatsuhiro; Higaki, Shunsuke; Inai, Reiko; Mochizuki, Susumu; Yoshihara, Akihide; Akimitsu, Kazuya (Journal of Food Technology Research, 2023)
Allitol, one of the sugar alcohols, is a rare sugar produced by reducing d-allulose contained in Itea, a deciduous shrub belonging to the Saxifrageaceae family. We previously found that the long-term feeding of rats with a diet supplemented with Itea powder suppressed obesity. The present study aimed to further investigate whether this effect on body fat accumulation may be attributed to the simultaneous intake of allitol and d-allulose in Itea. Thirty-two male 3-week-old Wistar rats were randomly divided into four groups of eight. The rats had ad libitum access to the control (C), 3% allitol (A), 3% d-allulose (P), or 3% allitol + 3% d-allulose (AP) diet for 8 weeks, after which the rats were euthanized. d-Allulose significantly lowered the final body weight, weight gain, and quantities of perirenal, mesenteric, and total abdominal adipose tissue. Allitol significantly decreased the mesenteric adipose tissue weight. However, we found no combined effect between d-allulose and allitol on all abdominal fat. The liver glucose-6-phosphate dehydrogenase activity was significantly higher in the d-allulose-supplemented groups. Cecal weight, surface area, and content weight were found to be significantly higher in Groups A and AP than those in Groups C and P, suggesting a higher intestinal fermentability of allitol. Our results suggest that allitol and d-allulose have anti-obesity properties that are affected through different mechanisms but are non-synergistic.